Nosocomial acinetobacter bacteraemia in HUSM - Harun, Azian; Deris, Zakuan Zainy; Johari, Mohd Radzi (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Acinetoliacter ''IPP is a known nosocomial pathogen causing a wide range of clinical diseases such as pneumonia, wound infeCti_On·and ·bloodstream infections (Bsn. The clinical outcomes of acinetobacter BSI were compared to · other gram negative infections. The crude mortality ofacinetobacter BSI was 47.2%, which was signitlcantly greater than other gfafn .. negative BSI. We found that patients treated in intensive care units (ICU), who had longer ICU stays, who preSented with shock or coagulopathy, had prior exposure to carbapenems, had mechanical ventilation, were on a ventilator tbr longer periods, had a nasogastric tube, had an arterial catheter or had parenteral nutrition at a significantly greatei- risk of mortality due to acinetobacter BSL Patients presenting with septic shock or having a central venous catheter were independently at higher risk for mortality. Appropriateness of therapy reduced the mortality attributes of acinetobacter BSJ but did not significantly reduce crude mortality in acinetobacter BSJ patients. This study shows the importance of preventing acinetobacter BSI and the appropriate use of antimicrobial agents to reduce mortality.